Modulation of endothelial cell signalling by chemically modified proteins - Banarjee, Reema (My University, 2018)
Chapter 1: Introduction Plasma proteins in vivo can react with number of endogenous metabolites as well as external entities like drugs which can lead to their chemical modification and affect their structure and function. Many such modified proteins are recognized by pattern recognition receptors like RAGE and LOX1 that function to remove the altered proteins from the system. However, under situations where there is excess of modifying agents, there can be over-accumulation of modified proteins. For example, hyperglycemia or elevated blood glucose levels in diabetes has been associated with elevated levels of glycated plasma proteins formed as a result of their reaction with glucose. Endothelial cells that line the vasculature are one of the first cells to interact with such modified plasma proteins. Accumulation of modified proteins in plasma can have deleterious effects on these cells and lead to endothelial dysfunction or ED. ED is characterized by a pro-inflammatory condition wherein there is vasoconstriction, thrombogenesis, leukocyte adhesion and vascular permeability which can act as an initial step in the development of vascular diseases. A number of risk factors of cardiovascular diseases are also associated with increased accumulation of modified proteins. For instance, higher level of glycated proteins in diabetic plasma can be an important contributing factor in the pathogenesis of diabetic cardiovascular complications. Understanding the mechanism of development of endothelial dysfunction in response to modified proteins can be useful in designing strategies for management of cardiovascular diseases. Therefore, in the present study, plasma proteins with different modifications were prepared and used to study the response of endothelial cells to treatment with such modified proteins. Chapter 2: Synthesis and Characterization of Different Chemically Modified Proteins Different metabolites and drugs have been reported to be capable of modifying proteins in plasma. Reducing sugars like glucose, and reactive metabolites formed during oxidative stress and lipid peroxidation, such as 4-hydroxynonenal and peroxynitrite can react with protein side chains and lead to the formation of adducts. Excess accumulation of modified proteins in plasma can have deleterious effects on the endothelial cells lining the vasculature culminating in vascular disorders. Therefore it is important to study the effects of different modifications on the protein structure as well as the effect of modified proteins on endothelial cells. For this reason, serum albumin, the most abundant plasma protein, was modified at number of residues by different modifying agents followed by characterization of the modified proteins by MALDI mass spectrometry, fluorescence spectroscopy, CD spectroscopy and western blot. The extent of modification and modification sites on albumin were identified by high resolution accurate mass spectrometry. The modifications also induced a change in the helical structure of albumin which was seen by CD spectroscopy. Treatment with modified albumin reduced the viability of endothelial cells. Thus modified plasma proteins can negatively affect endothelial cells and can predispose to endothelial dysfunction. Chapter 3: Study of Endothelial Dysfunction in Response to Glycated Albumin via RAGE and its Involvement in Diabetic Vascular Complications Diabetics have higher risk of developing cardiovascular diseases even with controlled blood glucose levels as compared to non-diabetics. Since ED acts as an initial step in the development of cardiovascular diseases, negative effects of glycated proteins on expression of proteins involved in endothelial functions such as vasodilation and blood coagulation can play a role in the development of diabetic cardiovascular complications. The interaction of glycated proteins with their receptor RAGE has already been implicated in the development of a number of conditions such as neurodegeneration and insulin resistance. Therefore, the effect of glycated albumin on endothelial cell function and global protein expression was studied. Glycated albumin induced oxidative stress and apoptosis in HUVECs. Further, proteomic analysis by SWATH MS identified 1860 proteins, of which 161 proteins showed higher abundance while 123 proteins showed lower abundance after treatment with glycated albumin. Among the proteins showing altered abundance were number of proteins involved in endothelial functions such as cell adhesion, platelet aggregation and angiogenesis, including ICAM-1 and vWF, which were also validated by quantitative PCR. Increased expression of the receptor RAGE was also observed by qPCR, along with nuclear translocation of Nf-κB which was seen by immunofluorescence. Thus, in this chapter, we could demonstrate the role of glycated proteins in inducing endothelial dysfunction and subsequent cardiovascular complications in diabetes. Chapter 4: Study of Endothelial Response to Homocysteinylated Albumin Folate deficiency is associated with hyperhomocystenemia, i.e. elevated levels of homocysteine, and an increased risk of cardiovascular diseases. Homocysteine thiolactone, a cyclic analogue of homocyteine formed as a result of its interaction with methionyl tRNA synthase, is reported to modify lysine side chains of proteins. Since homocysteine is present in blood in its protein bound form and not in free form, homocysteine modified proteins can play a role in the pathogenesis of cardiovascular diseases in patients with hyperhomocystenemia. Therefore, the effect of homocysteinylated proteins on endothelial cell function and its total cell proteome was studied. Homocysteinylated albumin induced oxidative stress and apoptosis in HUVECs. SWATH MS identified 1410 proteins out of which 53 proteins showed altered abundance including those involved in protein degradation pathways such as ubiquitin ligases and peptidases along with those involved in endothelial function. The differentially abundant proteins also included upstream regulators of Nf-κB which controls the expression of numerous mediators of endothelial dysfunction. Thus, prolonged presence of homocysteinylated proteins can lead to endothelial dysfunction. Chapter 5: Study of Modulation of Insulin Signal Transduction by Oxidized LDL via LOX-1 Interaction of oxidized LDL with its receptor LOX-1 plays an important role in the development of atherosclerosis. In endothelial cells, insulin signaling regulates a number of functions including expression and activation of eNOS, which is an important vasodilator and anti-inflammatory molecule and alteration of insulin signaling by LOX-1 can negatively affect eNOS functions. Therefore, the cross-talk between LOX1 and insulin signaling was studied using HEK293 cells over-expressing human LOX1 receptor. LOX-1 expressed in HEK293 cells could bind and internalize oxidized LDL as seen by immunofluorescence studies. Activation of signaling pathways in response to oxLDL binding to LOX1 was studied using western blot and a reduction in the phosphorylation of the serine/threonine kinase Akt could be observed. Additionally, insulin dependent pAkt activation was inhibited in the presence of oxidized LDL. Thus, interaction of oxLDL with LOX1 can negatively affect insulin mediated endothelial functions and lead to insulin resistance.
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology; Endothelial Dysfunction; Proteomics